Pengaruh Pendingin Udara Terhadap Kekerasan Dari Proses Solidifikasi Besi Cor Kelabu Dengan Cetakan Permanen - Setiawan, Muhammad Debi, Agus Yulianto, ST, MT, Dr. Supriyono (2016)
This research aims to know the rate of cooling on the solidification of gray cast iron in permanent mould for tapping earlier. This research uses a permanent mold cast iron ductile (FCD). Methodology this research was done by melting cast iron in induction furnace then pour in the mold of the FCD are already on preheating with a certain temperature for making grey cast iron specimen then tested the physical properties and mechanical. Testing in the form of grey cast iron using a liquid test CE Metres then in grey cast iron specimen in the test chemical composition with the spectrometer then tested the hardness and micro photographs taken of the direct contact with the air and direct contact with the mould the FCD. Research results in the form of graphs in the get from CE Meter shows the temperature 1356.8 ° C early in the process when tapping pour in mold at the start on the charts unreadable CE Meter temperature decline, at the temperature of liquid 1155.4 ° C liquid temperature until the shape is still solid 1113.6 ° C so that the values obtained in the CEL = 4.17%; C = 3,61%; and SI = 2,21% where the iron starts but still solid red until the temperature of 1060 ° C and harden within 180 seconds, while the chemical composition test results in the form of solid or solid, such as: Fe 93.46%; C 3.52%; SI 1.84% and other elements of under 1%. Test results of specimens that are part of the microstructure in uji violence visible graphite and sementit and hardness test results of specimens at the A = 148.79, 542.65, 162.21, 173.65, 207.02. B = 207.02, 168.06, 159.36, 263.85, 280.43. C = 206.28, 280.43, 211.07, 235.28, 682.28. and D = 682.28, 235.37, 215.25, 168.67, 148.79 and price the highest violence in part C5 and D1 amounting to 682.28, while the lowest rates of violence in parts of the A1 and D5 of 148.79. Based on these data can be conclude that every part has a level of violence that in price, because every point or part that has the content of carbon in the test. The higher the carbon content then it will be the higher level of violence as well as affect the physical properties of grey cast iron.